School autonomy in Portugal: The case of the educational community in Algoz – Silves - Rodríguez Miranda, Francisco de Paula; Pozuelos Estrada, Francisco José; García Prieto, Francisco Javier (Education Policy Analysis Archives, 2013)
Promulgated in 1976, the autonomy of the Portuguese education system has experienced many ups and downs ever since. Nowadays, in the context of the economic crisis, we are witnessing an orientation towards a strong bureaucratic regulation of the curriculum and its centralization. Despite this managerial paradigm, autonomy contracts reappeared with some potential for decentralization; in this paper we will discuss how far an educational community can go when it has autonomy, planning and management capability. This is the case-study of the school cluster of Algoz-Silves.